PERAN NILAI-NILAI MAQHASID SYARIAH DALAM PENANGGULANGAN KEMISKINAN DI TENGAH PANDEMI COVID 19 - Siti Khayisatuzahro Nur; Dimas Herliandis Shodiqin (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2022)
The problem of poverty in Indonesia is certainly crucial and results in the country's economic slowdown. Various poverty alleviation programs were initiated by the National Team for the Acceleration of Poverty Reduction (TNP2K). The poverty alleviation model has been implemented and has had a positive impact on reducing poverty in Indonesia. In line with the program, Islam is present as a means of achieving community welfare within the scope of sharia by using the values ​​of Maqashid Sharia. The research method used in this research is descriptive research with a library research approach. The results of this study are: (1) the poverty reduction program is divided into 4 models of poverty alleviation stages, namely the social assistance development model, community empowerment development model, and micro-enterprise empowerment model (2) poverty reduction program by applying Maqashid Syariah values ​​in accordance with the Maqashid Syariah principles described in 5 basic concepts, namely guarding religion, guarding reason, protecting soul, protecting offspring, and safeguarding property. Internalization of Maqashid Syariah values ​​in poverty alleviation can be achieved to realize the benefit for the community.